2018
DOI: 10.1590/1678-5150-pvb-5283
|View full text |Cite
|
Sign up to set email alerts
|

Detection and genetic identification of pestiviruses in Brazilian lots of fetal bovine serum collected from 2006 to 2014

Abstract: The present study performed a genetic identification of pestiviruses contaminating batches of fetal bovine serum (FBS) produced in Brazil from 2006 to 2014. Seventy-three FBS lots were screened by a RT-PCR targeting the 5’untranslated region (UTR) of the pestivirus genome. Thirty-nine lots (53.4%) were positive for pestivirus RNA and one contained infectious virus. Nucleotide sequencing and phylogenetic analysis of the 5’UTR revealed 34 lots (46.6%) containing RNA of bovine viral diarrhea virus type 1 (BVDV-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 22 publications
1
33
0
1
Order By: Relevance
“…Finally, phylogenetic analysis of all 21 HoBiPeV genomes, amplified by 5′ UTR primers N2-R5, grouped them together and in the same genetic group of several previously described Brazilian sequences, subgroup 3a (Fig. 3) [24,27,29,31].…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Finally, phylogenetic analysis of all 21 HoBiPeV genomes, amplified by 5′ UTR primers N2-R5, grouped them together and in the same genetic group of several previously described Brazilian sequences, subgroup 3a (Fig. 3) [24,27,29,31].…”
Section: Resultsmentioning
confidence: 75%
“…Phylogenetic analysis of BVDV-2 sequences amplified by primers 90-368 [9] and BVDV2#3 [24] grouped them in the BVDV-2b subgenotype (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil seems to have an important role on the HoBiPeV description in other countries. In 2004, the HoBiPeV was first identified in Europe, in FBS imported from Brazil (Schirrmeier et al, 2004), and to date, more than one‐third of all HoBiPeV identified in the world have come from FBS, labelled as having a Brazilian or (broadly) South American origin (Bauermann et al, 2013; Jardim et al, 2018; Monteiro et al, 2018; Silveira et al, 2017). This fact could be explained by an increase of the Brazilian bovine population in the 1970s (ABIEC, 2016) and a increasing exportation of Brazilian bovine products to several countries.…”
Section: Discussionmentioning
confidence: 99%
“…Most RT-PCR assays for pestivirus detection target the highly conserved 5'-UTR. 5,7,[11][12][13]19 826299V DIXXX10.1177/1040638719826299Pestivirus detection with pan-bovine pestivirus primersMonteiro et al We employed a newly designed set of primers (BP189-389) to screen the sera of beef calves for pestiviruses in a gel-based RT-PCR. Serum samples positive for BVDV antigens in an antigen ELISA (n = 135) were submitted to RT-PCR using different sets of primers targeting the 5'-UTR of the viral genome (Table 1).…”
mentioning
confidence: 99%